2023
DOI: 10.4097/kja.22669
|View full text |Cite
|
Sign up to set email alerts
|

Erector spinae plane versus fascia iliaca block after total hip arthroplasty: a randomized clinical trial comparing analgesic effectiveness and motor block

Abstract: This article has been accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination, and proofreading processes, which may lead to differences between this version and the version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Chronic back pain, instability, neurogenic claudication, as well as radicular symptoms can appear due to its connection with spinal stenosis of lumbar secondary to LDS resulting in nerve root compression. [ 12 , 13 ] Since various treatment modalities have been used recently, there has been a long debate over the treatment of LDS. [ 14 ] In few previous studies, there have been outcome comparison between SM and NSM in patients with LDS.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic back pain, instability, neurogenic claudication, as well as radicular symptoms can appear due to its connection with spinal stenosis of lumbar secondary to LDS resulting in nerve root compression. [ 12 , 13 ] Since various treatment modalities have been used recently, there has been a long debate over the treatment of LDS. [ 14 ] In few previous studies, there have been outcome comparison between SM and NSM in patients with LDS.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, few studies have compared L-ESPB and FICB in total hip replacement surgeries. Flaviano et al [15] concluded that Both L-ESPB and FICB have comparable advantages in reducing the need for opioids during the initial 24 hours following surgeries. Nevertheless, L-ESPB leads to less deterioration in the quadriceps motor function.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast material spread to the paravertebral, foraminal, and partially epidural area/spaces and in the areas where the lumbar nerves enter the psoas muscle which may hint at the mechanism of analgesia of the block [ 38 ]. The lumbar ESP block has shown similar analgesia to the infra-inguinal fascial iliaca block after elective hip arthroplasty with the potential for motor sparing of the quadriceps muscle [ 39 ]. A recent meta-analysis concluded that the use of the lumbar ESP block resulted in reduced opioid consumption in the first 24 h after surgery with significantly lower pain scores in the first 8 h after surgery [ 40 ].…”
Section: Peripheral Nerve Blocksmentioning
confidence: 99%